The Effect of Leadership Style on Improving Employee Performance - Na'im, Arif Ainun; Febrian, Angga; Firdaus, Luthfi; Marvinita, Risda; Mardiana, Nova (International Research Journal of Business Studies, 2023)
Leadership style significantly impacts the organization's long-term viability. On the other hand, leadership style can also affect an organization's reputation. This study intends to investigate the relationship between corporate reputation and leadership style, which has consequences for raising worker productivity. An online poll targeting employees in different work units and businesses in Indonesia was used to obtain the data. The study's findings can advance understanding, particularly in terms of the way that corporate reputation mediates the relationship between leadership style and employee performance. This research also has practical implications for management in an organization to be more aware of the role of organizational reputation that can influence employee performance. In addition, the quality of leaders is also one of the main drivers of organizational reputation, so a good reputation will create a climate of fair work competition for employees to improve their performance.